ANALISIS KOSA KATA YANG BERHUBUNGAN DENGAN GENDER DALAM BAHASA INGGRIS DAN BAHASA SANGIR (SUATU ANALISIS KONTRASTIF) - MOKODOMPIS, ANISTASYA; PELEALU, HETTY; MARENTEK, ANDRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThe study entitled â€œGender in English and Sangir Language (A Contrastive Analysis)â€ is an attempt to identify, analyze, describe and contrast English and Sangir Language which focuses on gender. The writer analyzed the gender based on the concept of Trudgill (1987), and contrasted by using Ladoâ€™s theory (1957). The aims of this study are to describe the relationship between gender and language which focuses on vocabulary and to find out the differences between the two languages. The results of this research show that English language has six categories of gender, namely: occupations, nouns, term of address, adjectives, personal pronouns and the name of animals in the form of masculine, feminine and neutral. Sangir language has seven categories of gender, namely: term of address, adjectives, nouns, verb, occupations, name of animals and personal pronouns in the form of masculine, feminine, and neutral. The differences of both languages can be seen in Sangir language which has gender-related verbs, but English does not have any.Â Key words: Ethnolinguistic, Gender, Contrastive Analysis, English, Sangir Language.